Precision agriculture : a study of the profitability in a Swedish context - Karlsson, Anton; Nessvi, Christoffer (SLU/Dept. of Economics, 2018)
A comparison within the European Union (EU), reveals that the Swedish agricultural sector is at a lower rate than other comparable countries regarding competitiveness. The low rate of competitiveness is an adverse development for Sweden, and according to a yearly report created by LRF Konsult the profitability of Swedish grain farming is low (SJV, 2014; www, LRF, 2017). One method to improve the profitability in the agricultural sector is to apply precision agriculture to the operation (Zarco-Tejada et al., 2014).